Work stress and health problems of professional drivers: A hazardous formula for their safety outcomes (2018)
Background Several empirical studies have shown that professional drivers are a vulnerable occupational group, usually exposed to environmental stressors and adverse work conditions. Furthermore, recent studies have associated work-related stress with negative job performances and adverse health outcomes within this occupational group, including cardiovascular diseases and unsafe vehicle operation. Objective The aim of this study was to describe the working conditions and the health status of this occupational group, and to evaluate the association between the Demand–Control model of job stress and their self-reported health and safety outcomes. Methods A pooled sample of 3,665 Colombian professional drivers was drawn from five different studies. The Job Content Questionnaire and the General Health Questionnaire were used to measure work stress and self-reported mental health, respectively. Additionally, professional drivers self-reported health problems (hypertension, dyslipidemia, diabetes and overweight) and health-related risky behaviors (smoking and sedentary behavior). Results Regarding the Job Demands–Control (JDC) model, it was found that approximately a third part of Colombian professional drivers suffer from high job strain (29.1%). Correlational and multivariate analyses suggest that de JDC model of stress is associated with the professional drivers’ mental health, traffic accidents and fines, but not with other physical and behavioral health-related outcomes, which are highly prevalent among this occupational group, such as hypertension, dyslipidemia, diabetes, overweight, smoking and sedentary behavior. Conclusion The results of this study suggest that (a) stressful working conditions are associated with health and lifestyle-related outcomes among professional drivers, and (b) that evidence-based interventions are needed in order to reduce hazardous working conditions, job stress rates and their negative impact on the health of this occupational group